2007
DOI: 10.1007/s10620-007-9984-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ras Inhibition on the Proliferation, Apoptosis and Matrix Metalloproteases Activity in Rat Hepatic Stellate Cells

Abstract: In vivo inhibition of Ras by its antagonist farnesylthiosalicylic acid (FTS) prevents and reverses liver fibrosis in a rat model. In this study we showed the in vitro effects of Ras inhibition in a rat hepatic stellate cell line, HSC-T6. The IC(50) of FTS that inhibited PDGF-induced proliferation was 15 microM. FTS, by itself or in combination with PDGF, induced a three- to fivefold increase in the number of apoptotic stellate cells but did not induce apoptosis in cells cultured with TGFbeta1. We observed incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…In a model of liver cirrhosis induced by thioacetamide in rats, FTS had preventive qualities by inhibiting hepatic stellate cell activation and proliferation [20]. In the same model, FTS was found to be an effective treatment, partially reversing liver cirrhosis by reducing collagen secretion and up-regulating metalloproteinase activity [19,27]. In the current study, we found that FTS had a beneficial effect on the inflammatory process of experimentally induced colitis in mice.…”
Section: Discussionsupporting
confidence: 51%
“…In a model of liver cirrhosis induced by thioacetamide in rats, FTS had preventive qualities by inhibiting hepatic stellate cell activation and proliferation [20]. In the same model, FTS was found to be an effective treatment, partially reversing liver cirrhosis by reducing collagen secretion and up-regulating metalloproteinase activity [19,27]. In the current study, we found that FTS had a beneficial effect on the inflammatory process of experimentally induced colitis in mice.…”
Section: Discussionsupporting
confidence: 51%
“…Additional examples are the up-regulation in infected animals of genes encoding the TGF-β1 and its Induced Transcript 1 (TGF-β1I1) as well as the chemokines CCL3 and CCL4. In addition to its roles in regulating T-cell differentiation (see above), TGF-β1 is also relevant in fibrosis [ 99 - 102 ]. CCL3 and CCL4 are expressed by a number of cell types, including activated B cells, monocytes, mast cells, fibroblasts and epithelial cells [ 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…HSCs, the main source of ECM, play important roles in the formation of hepatic fibrosis (Fischer et al, 2001;Issa et al, 2001;Vincent et al, 2001;Zvibel et al, 2008). We recently demonstrated that YiGanKang Decoction inhibit liver fibrosis via HSCs inhibition (Yao et al, 2002aWang et al, 2005;Yao and Lv, 2005).…”
Section: Introductionmentioning
confidence: 99%